Episodic foresight and schizophrenia. (14th July 2015) - Lyons, Amanda D.; Henry, Julie D.; Rendell, Peter G.; Robinson, Gail; Suddendorf, Thomas
Abstract : Objective: People with schizophrenia have difficulty engaging in specific future‐directed thoughts and behaviours, such as generating phenomenological characteristics of future events (a component of episodic foresight), and executing directed preparatory behaviours (a component of prospective memory). However, it remains unclear whether they also exhibit difficulties using episodic foresight to appropriately guide future‐directed behaviours. Method: People with schizophrenia and non‐clinical controls were administered a behavioural measure that met strict criteria for assessing episodic foresight. In keeping with our focus on the functional application of foresight, this measure required participants to identify a problem, self‐generate a resolution, and execute the appropriate future‐directed intention. Results: Relative to controls, people with schizophrenia were less likely to spontaneously acquire items that would later allow a problem to be solved, and were also less likely to subsequently use these items to solve the problems. There was no interaction between group and task, indicating that these two components of foresight were disrupted to an equivalent degree. In the clinical (but not the control) group, item acquisition and item use were correlated with general cognitive capacity. No significant associations with clinical variables emerged. Conclusion: The capacity to apply episodic foresight in a functionally adaptive way is disrupted in schizophrenia and may at least partially reflect broader cognitive dysfunction. Future work is now needed to clarify the implications of these difficulties in everyday life, as well as how these difficulties might be remediated. Practitioner points: People with schizophrenia have known difficulties with episodic foresight, and it now appears that those difficulties extend to the performance of foresightful preparatory behaviours. Because preparatory behaviours are central to routine and adaptive planning, difficulties with episodic foresight may contribute to or be a result of some of the functional difficulties experienced by people with schizophrenia. Further research is needed to determine whether interventions might be developed for people with reduced episodic foresight. Interventions may include the use of remedial tools that support and encourage the performance of foresightful behaviour, or cognitive training programs that actively improve the ability and propensity to exercise foresight independently.